Leadership Styles and Employee Engagement: A Management Perspective in the Service Industry - Sana, Eirene; Ming, Li Wei; Hernandez, Daniel; Kask, Rasmus (Pandawan, 2024)
This study delves into the relationship between leadership styles and employee engagement within the service sector. Employing a qualitative approach, the research involved in-depth interviews with 50 respondents from diverse service organizations. The findings underscore that transformational leadership, emphasizing inspiration and individual development, significantly impacts employee engagement. Transactional leadership, which centers on rewards and punishments, also influences engagement, albeit to a lesser degree. Conversely, laissez-faire leadership, characterized by minimal intervention and full autonomy for employees, exhibits the weakest impact. These findings emphasize the significance of deploying suitable leadership styles to bolster employee engagement and performance in service-oriented industries. The study offers practical insights for managers seeking to cultivate effective leadership strategies, thereby nurturing supportive and motivating work environments conducive to enhancing overall organizational performance. By comprehending the ramifications of different leadership approaches, managers can better steer their organizations toward success in industries reliant on human interaction. Thus, this research not only enriches the academic discourse on leadership and employee engagement but also furnishes pragmatic guidance for practitioners in the service industry to tailor leadership practices according to their organizational dynamics, fostering sustainable growth and success.